Correcting the Scholarly Record for Research Integrity In the Aftermath of Plagiarism - Dougherty, M. V. (Research Ethics Forum,, 2018)
This volume is the first book-length study on post-publication responses to academic plagiarism in humanities disciplines. It demonstrates that the correction of the scholarly literature for plagiarism is not a task for editors and publishers alone; each member of the research community has an indispensable role in maintaining the integrity of the published literature in the aftermath of plagiarism. If untreated, academic plagiarism damages the integrity of the scholarly record, corrupts the surrounding academic enterprise, and creates inefficiencies across all levels of knowledge production. By providing case studies from the field of philosophy and related disciplines, the volume exhibits that current post-publication responses to academic plagiarism are insufficient. It catalogues how humanities disciplines fall short in comparison with the natural and biomedical sciences for ensuring the integrity of the body of published research. This volume provides clarity about how to conceptualize the scholarly record, surveys the traditional methods for correcting it, and argues for new interventions to improve the reliability of the body of published research. The book is valuable not only to those in the field of philosophy and other humanities disciplines, but also to those interested in research ethics, meta-science, and the sociology of research.